Is transplanetary sustainability a good idea? An answer from the perspective of conceptual engineering. Issue 5 (4th January 2019) - Beisbart, Claus
Abstract: Is our current concept of sustainable development too focused on our planet? Do we need a new conception of sustainability? The recent call for an 'ethics of planetary sustainability' by A. Losch may be understood as promoting an affirmative answer to this question. This essay analyses and assesses the introduction of a new concept of sustainability from the perspective of conceptual engineering. The central question is whether this new concept, which I call 'transplanetary sustainability', may improve our thinking, and, indirectly, our practices. I argue that a new notion of transplanetary sustainability advantageously points to considerations that matter from a moral point of view. It may also help us to be more exact and consistent in our moral thinking. At the same time, there are serious doubts as to how fundamental the concept of sustainability as such is from a theoretical perspective since it does not figure in prominent moral theories. Furthermore, in view of possible extraterrestrial beings that deserve to be taken into account from a moral point of view, the proposed revision of the concept may reach less than required. Nevertheless, since sustainability has had an impressive career in international politics, it is practically speaking important that sustainability be conceived such that outer space is taken into account.